Indoor Environmental Quality, Occupants’ Satisfaction And Perceived Productivity In Green Building Index Rated Office Buildings - Tharim, Asniza Hamimi Abdul (2018)
The aim of this research is to examine the objective and subjective measurements of overall indoor environmental quality (IEQ) in Green Building Index (GBI) Non-Residential New Construction (NRNC) office buildings located in Kuala Lumpur and Putrajaya, Malaysia. This is also to identify the influence of various façade designs that are implemented in the selected GBI NRNC office buildings. This research not only focuses on the aspects of the IEQ levels in the selected case study buildings, but it also tests the relationship between IEQ and Occupants’ Perceived Productivity with Occupants’ Satisfaction as mediator. The research methodology adopted for this research is divided into two types which are the objective (fieldwork) and subjective (questionnaire survey in the form of post occupancy evaluation) measurements. Subsequently, in order to investigate the current performance of IEQ in the selected GBI NRNC office buildings, a series of fieldwork measurement were conducted in the buildings i.e., ST Building, PJH Building, MITI Building and KKR2 Building. Indoor and outdoor environments were monitored in this research to evaluate the IEQ performance of these building with various façade design. Concurrently, the POE survey on IEQ assessment were distributed and collected amongs occupants in the buildings. Using the purposive sampling techniques, 302 responses were analyzed using the partial least squares structural equation modeling.